The Influence of Country of Origin, Advertising Campaign, and Brand Ambassador on Customers Purchase Intention in Digital Marketplace Official Site - Luh Komang Candra Dewi; Sherry Adelia; I Gede Anindya Perdana Putra; Helmi Ali; Musran Munizu (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The objective of this investigation is to assess the effect of endorsers, promotional activities, and nation of origin on the inclination to buy. The fundamental wellspring of information for this examination is essential information gathered from a gathering of female understudies who have bought things on the web. The questionnaire was administered to 200 respondents through purposive sampling. The data was scrutinized using multiple linear regression analyses. The findings reveal that endorsers and promotional activities have a significant effect on purchase intention, whereas nation of origin does not. Furthermore, endorsers, promotional activities, and nation of origin all have a noteworthy impact on purchase intention. Based on the coefficient of determination, 68% of the independent variable contributes to purchase intention, while the remaining 32% is influenced by other variables that were not examined in this research.